Composite lithium battery diaphragm

The composite lithium battery separator with a multi-layered nanofiber membrane and inorganic coatings addresses issues of thermal stability and dendrite growth, ensuring uniform ion flow and improved safety and mechanical strength.

CN222282177UActive Publication Date: 2024-12-31HEBEI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420605668.8
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2024-12-31
Estimated Expiration
2034-03-27

AI Technical Summary

Technical Problem

Existing lithium battery separators suffer from poor thermal stability, flammability, and uneven lithium ion transmission, leading to lithium dendrite growth, which compromises safety and mechanical integrity.

Method used

A composite lithium battery separator with a multi-layered oriented nanofiber membrane structure, featuring decreasing pore sizes from the center to the sides, combined with inorganic outer coatings, ensures uniform lithium ion flow and mechanical strength to inhibit dendrite growth.

Benefits of technology

The composite separator achieves uniform lithium ion deposition, enhances mechanical properties, and improves thermal stability and safety by synergistically inhibiting lithium dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222282177U_ABST
    Figure CN222282177U_ABST
Patent Text Reader

Abstract

The composite lithium battery diaphragm comprises a first outer coating, a composite inner membrane and a second outer coating which are sequentially arranged in a stacked mode, the first outer coating and the second outer coating are both inorganic nanometer coatings, and the upper surface and the lower surface of the composite inner membrane are coated with the first outer coating and the second outer coating respectively; the composite inner membrane comprises at least three layers of fiber membranes which are bonded in sequence, and each layer of fiber membrane is an oriented nanofiber membrane; the pore diameters of the composite lithium battery diaphragm are respectively reduced layer by layer along the extending direction from the central surface of the thickness direction of the composite lithium battery diaphragm to the two sides; and in the projection of the fiber orientation direction of each layer of fiber membrane at any point on the central plane, the projection of each orientation direction is circumferentially and uniformly distributed by taking the any point as the center. According to the invention, lithium ions can uniformly flow, formation and growth of lithium dendrites are effectively inhibited, the mechanical property of the composite lithium battery diaphragm is improved, and the stability and safety of a lithium battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of lithium battery diaphragms, in particular to a composite lithium battery diaphragm. Background Art

[0002] Lithium battery separator is a polymer film with micro-nano pores. Its main function is to block the positive and negative electrodes to prevent the two electrodes from contacting and causing internal short circuits. It can also retain the necessary electrolyte and form a channel for the movement of lithium ions. It is a key internal component of lithium batteries. The ionic conductivity, thermal safety performance and tensile strength along the winding direction of the lithium battery separator play a vital role in the safety and electrochemical performance of lithium batteries.

[0003] The existing commercial lithium battery separators mainly include polyethylene (PE) separators, polypropylene (PP) separators, and PE and PP composite multi-layer microporous membranes, which have poor thermal stability and are flammable. After assembling batteries, they pose a great safety hazard. In addition, lithium batteries generally have the problem of lithium dendrites. The uneven transmission of lithium ions will cause uneven deposition of lithium ions at the negative electrode of the battery. The uneven deposition of lithium ions is one of the main reasons for the growth of lithium dendrites. The growth of lithium dendrites will pierce the separator, seriously affecting the safety of the battery. In related technologies, a ceramic layer is usually coated on the surface of the separator to hinder the growth of lithium dendrites, so as to achieve the purpose of inhibiting the growth of lithium dendrites.

[0004] In the above technical scheme, coating a ceramic layer on the surface of the lithium battery separator cannot fundamentally inhibit the growth of lithium dendrites. The existing lithium battery separators still have deficiencies in thermal stability and flammability and other safety aspects, and the problem of uneven lithium ion transmission still exists; in addition, coating the ceramic layer also increases the overall thickness, weight and brittleness of the separator to a certain extent, which is not conducive to practical application. Utility Model Content

[0005] In order to solve at least one of the problems mentioned in the background technology, an embodiment of the present application provides a composite lithium battery separator, the pore size of the composite lithium battery separator decreases layer by layer from the center to both sides along the thickness direction, and the layers of the membrane are arranged regularly. The composite inner membrane is a multi-layer oriented nanofiber membrane with good mechanical properties and high porosity. At the same time, the uniform flow of lithium ions can effectively inhibit the formation of lithium dendrites in lithium batteries. The outer coating has high hardness and rigidity, which can effectively hinder the growth of lithium dendrites. The outer coating and the composite inner membrane work together to achieve synergistic inhibition of lithium dendrites, thereby improving the mechanical properties of the composite lithium battery separator and improving the stability and safety of the lithium battery.

[0006] The embodiment of the present application provides a composite lithium battery separator, comprising a first outer coating, a composite inner film, and a second outer coating stacked in sequence, wherein the first outer coating and the second outer coating are both inorganic nano coatings, and the first outer coating and the second outer coating are respectively coated on the upper and lower surfaces of the composite inner film;

[0007] The composite inner membrane comprises at least three layers of fiber membranes bonded in sequence, and each layer of the fiber membranes is an oriented nanofiber membrane;

[0008] Along the center surface of the thickness direction of the composite lithium battery separator and the direction extending to both sides, the pore size of the composite lithium battery separator decreases layer by layer;

[0009] In the projection of the fiber orientation direction of each layer of the fiber membrane at any point on the central plane, the projections of each orientation direction are evenly distributed in a circle with the arbitrary point as the center.

[0010] In a feasible implementation, the total thickness of the composite lithium battery separator is 25 to 45 micrometers, and the number of layers of the fiber membrane is 3 to 8 layers.

[0011] In a feasible embodiment, the composite inner membrane includes four layers of fiber membranes, and the four layers of fiber membranes are a first fiber membrane, a second fiber membrane, a third fiber membrane and a fourth fiber membrane arranged in sequence between the first outer coating layer and the second outer coating layer.

[0012] In a feasible implementation, the pore size of the second fiber membrane and the third fiber membrane is 200-500 nanometers, the pore size of the first fiber membrane and the fourth fiber membrane is 50-200 nanometers, and the pore size of the first outer coating layer and the second outer coating layer is 10-50 nanometers.

[0013] In a feasible embodiment, the fiber orientation direction of the first fiber membrane is consistent with the length direction of the composite inner membrane, the fiber orientation direction of the second fiber membrane is at an angle of 45° to the fiber orientation direction of the first fiber membrane, the fiber orientation direction of the third fiber membrane is perpendicular to the fiber orientation direction of the second fiber membrane, and the fiber orientation direction of the fourth fiber membrane is perpendicular to the fiber orientation direction of the first fiber membrane.

[0014] In a feasible implementation, each layer of the fiber membrane is connected to form an integrated structure by a binder, and the binder includes soluble polyvinylidene fluoride and inorganic nanoparticles.

[0015] In a feasible implementation, each layer of the fiber membrane is made of polyimide material using electrospinning technology.

[0016] In a feasible implementation, the first outer coating layer is made of an inorganic material on the upper surface of the composite inner membrane by a scraping process, and the second outer coating layer is made of an inorganic material on the lower surface of the composite inner membrane by a scraping process.

[0017] In a feasible implementation, the inorganic materials used for the first outer coating layer and the second outer coating layer are boron nitride and / or graphene oxide.

[0018] In summary, the pore size of the composite lithium battery separator provided by the present application decreases layer by layer from the center to both sides along the thickness direction, and the composite inner membrane is a multi-layer oriented nanofiber membrane, and the fiber orientation direction of each layer of the fiber membrane is uniformly distributed in the circumferential direction. The lithium ions in the electrolyte pass through the small holes to reach the large holes and are stored and then flow out through the small holes, so that the lithium ions enter and flow out of the composite lithium battery separator uniformly. The uniform flow of lithium ions helps to uniformly deposit lithium ions, thereby effectively inhibiting the formation of lithium dendrites. Each layer of the fiber membrane has good mechanical properties and high porosity, and the outer coating with high hardness and rigidity can further hinder the growth of lithium dendrites. The outer coating and the composite inner membrane work together to achieve synergistic inhibition of lithium dendrites, thereby improving the mechanical properties of the composite lithium battery separator and improving the stability and safety of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0020] Figure 1 A schematic diagram of the structure of a composite lithium battery separator provided in an embodiment of the present application;

[0021] Figure 2 A lithium deposition test of a lithium diaphragm of a composite lithium battery provided in an embodiment of the present application;

[0022] Figure 3 This is a stress curve of the lithium diaphragm of the composite lithium battery provided in the embodiment of the present application.

[0023] Description of reference numerals:

[0024] 10 - first outer coating layer; 20 - composite inner membrane; 21 - first fiber membrane; 22 - second fiber membrane; 23 - third fiber membrane; 24 - fourth fiber membrane; 30 - second outer coating layer. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution in the embodiment of the present application will be described in more detail below in conjunction with the drawings in the embodiment of the present application. It is worth noting that the embodiments described in the drawings are only part of the embodiments of the present application, not all of the embodiments. That is, the embodiments described by the drawings are exemplary and are intended to be used to explain the present application, and cannot be understood as limiting the present application.

[0026] The following will be combined Figure 1 to Figure 3 The composite lithium battery separator provided in the embodiments of the present application is described.

[0027] The present application embodiment provides a composite lithium battery separator, such as Figure 1 As shown, it includes a first outer coating 10, a composite inner film 20 and a second outer coating 30 which are stacked in sequence. The first outer coating 10 and the second outer coating 30 are both inorganic nano coatings, and the first outer coating 10 and the second outer coating 30 are respectively coated on the upper and lower surfaces of the composite inner film 20.

[0028] The composite inner membrane 20 includes at least three layers of fiber membranes bonded in sequence, and each layer of the fiber membrane is an oriented nanofiber membrane.

[0029] Along the direction extending from the center surface to both sides of the thickness direction of the composite lithium battery separator, the pore size of the composite lithium battery separator decreases layer by layer.

[0030] In the projection of the fiber orientation direction of each layer of fiber membrane at any point on the central plane, the projections of each orientation direction are evenly distributed in a circle with the arbitrary point as the center.

[0031] Among them, the oriented nanofiber membrane is prepared by the following electrospinning technology under specific conditions such as rotation speed and voltage. The fibers of the same layer of oriented nanofiber membrane are arranged in an orderly manner along the same direction, which is called the orientation direction. The fiber arrangement of the same layer of fiber membrane has a high degree of orientation and better performance.

[0032] The multiple layers of fiber membranes are regularly stacked and connected in a way that the fiber orientation directions of each layer of fiber membranes are different from each other. The projections of the fiber orientation directions of each layer of fiber membranes on the central plane are evenly distributed in a circle to ensure that the mechanical properties of the composite inner membrane are consistent in all directions, so that the overall stress of the diaphragm is large and the tensile strength is high.

[0033] The pore size of each layer of fiber membrane is achieved by adjusting the electrospinning conditions. The pore size decreases from the center to both sides along the thickness direction, providing conditions for the uniform flow of lithium ions. For example, when the number of fiber membrane layers is an odd number, the pore size of the fiber membrane in the middle is the largest, and then the pore size of the fiber membranes on both sides decreases in the outward direction. When the number of fiber membrane layers is an even number, the pore size of the two fiber membranes in the middle is the largest, and then the pore size of the fiber membranes on both sides decreases in the outward direction.

[0034] The pore size of the composite lithium battery separator provided by the present application decreases layer by layer from the center to both sides along the thickness direction, and the composite inner membrane is a multi-layer oriented nanofiber membrane, the fiber orientation direction of each layer of the fiber membrane is uniformly distributed in the circumferential direction, and each layer of the fiber membrane has good mechanical properties and chemical stability. The large pore size in the middle can better store the electrolyte, and the small pore size on both sides can allow lithium ions to flow in and out evenly, realizing the uniform flow of lithium ions, which is conducive to the uniform deposition of lithium ions, and further inhibiting the formation of lithium dendrites. The outer coating with higher hardness and rigidity can further hinder the growth of lithium dendrites.

[0035] The composite lithium battery separator of the present application was subjected to lithium deposition test, and the test results are as follows: Figure 2 As shown in the figure, the horizontal axis is time and the vertical axis is voltage, indicating that the battery is at 1mA / cm 2 The overpotential of the composite lithium battery separator is significantly lower than that of the commercial separator, indicating that the composite lithium battery separator of the present application has good lithium dendrite inhibition function.

[0036] The composite lithium battery separator of the present application was subjected to stress testing, and the test results are as follows: Figure 3 As shown, the horizontal axis in the figure is strain and the vertical axis is stress. The composite lithium battery separator of the present application has high stress and high tensile strength, thus having better mechanical properties.

[0037] The composite lithium battery separator of the present application has excellent tensile strength, which solves the problem of poor mechanical properties of nanofiber membranes. In addition, the composite lithium battery separator of the present application also realizes uniform flow of lithium ions, and the outer coating and the composite inner membrane work together to achieve synergistic inhibition of lithium dendrites, thereby improving the stability and safety of lithium batteries.

[0038] In a feasible implementation, the total thickness of the composite lithium battery separator is 25 to 45 microns, and the number of fiber membrane layers is 3 to 8.

[0039] Among them, in combination with the requirements of the thickness of the separator for commercial batteries in practical applications in this field, and taking into account the processing and manufacturing level, the thickness of the fiber membrane can be set to 5 to 10 microns, and the overall thickness is 25 to 45 microns. This setting can further improve operability and applicability.

[0040] In one possible implementation, Figure 1 As shown, the composite inner membrane 20 includes four layers of fiber membranes, which are a first fiber membrane 21, a second fiber membrane 22, a third fiber membrane 23 and a fourth fiber membrane 24 arranged in sequence between the first outer coating 10 and the second outer coating 30.

[0041] With this arrangement, the composite lithium battery separator is composed of four layers of fiber membranes and two layers of outer coatings arranged in a regular pattern. The mechanical properties of the composite lithium battery separator are consistent in all directions, further improving the tensile strength and overall stability of the separator.

[0042] In a feasible implementation, the pore size of the second fiber membrane 22 and the third fiber membrane 23 is 200-500 nanometers, the pore size of the first fiber membrane 21 and the fourth fiber membrane 24 is 50-200 nanometers, and the pore size of the first outer coating 10 and the second outer coating 30 is 10-50 nanometers.

[0043] This arrangement provides suitable spatial conditions for the circulation of lithium ions, enables uniform and stable circulation of lithium ions, and improves operability and safety.

[0044] In a feasible embodiment, the fiber orientation direction of the first fiber membrane 21 is consistent with the length direction of the composite inner membrane 20, the fiber orientation direction of the second fiber membrane 22 is at an angle of 45° to the fiber orientation direction of the first fiber membrane 21, the fiber orientation direction of the third fiber membrane 23 is perpendicular to the fiber orientation direction of the second fiber membrane 22, and the fiber orientation direction of the fourth fiber membrane 24 is perpendicular to the fiber orientation direction of the first fiber membrane 21.

[0045] This arrangement further improves the overall mechanical properties of the diaphragm and facilitates processing and manufacturing.

[0046] In a feasible implementation, each layer of fiber membrane is connected to form an integrated structure by a binder, and the binder includes soluble polyvinylidene fluoride (PVDF) and inorganic nanoparticles.

[0047] Among them, PVDF in the binder has the function of adhering inorganic nanoparticles to the fiber surface; the inorganic nanoparticles in the binder can be selected from one or more of boron nitride, graphene oxide, silicon dioxide, titanium dioxide and other substances, and the embodiment of the present application preferably uses boron nitride.

[0048] The preparation process of the composite inner membrane 20 is as follows: the arranged multi-layer nanofiber membrane is fixed to the iron ring, and the whole is immersed in an impregnation liquid containing a binder for 5 to 10 minutes, and then the impregnated multi-layer fiber membrane is dried in an environment of 50 to 80 degrees.

[0049] The impregnation process is carried out under ultrasonic conditions, and the inorganic nanoparticles will evenly adhere to the surface of the nanoparticles in each layer of the film along with the impregnation liquid, and at the same time, the inorganic nanoparticles achieve adhesion between the films under ultrasonic dispersion. In this way, a composite inner film 20 with a multi-layer integrated structure is prepared by controlling the content of PVDF and inorganic nanoparticles.

[0050] In a feasible implementation, each layer of fiber membrane is made of polyimide material using electrospinning technology.

[0051] Among them, polyimide (PI) has high mechanical properties, high and low temperature resistance, low dielectric constant, radiation resistance and other properties. By adjusting the electrospinning conditions to prepare PI fiber membranes with different pore sizes and orientation, the performance of the composite lithium battery separator can be further improved.

[0052] Exemplarily, the preparation process of an oriented PI fiber membrane with a pore size of 50 to 200 nanometers is as follows: first, 1.9621 g of ODA (diaminodiphenyl ether) is dissolved in DMAc (dimethylacetamide) in an ice water bath, and then 2.1438 g of PMDA (pyromellitic anhydride) monomer is gradually added to the above solution, and a PAA (acrylic resin) solution with a solid content of 8% is prepared by gradual polymerization. The PAA solution obtained by polymerization is transferred to a syringe as a spinning solution, the spinning voltage is set to 20 kV, the distance between the spinning needle and the receiving roller is set to 15 cm, the receiving roller speed is set to 1500 to 2000 rpm, and then the PAA fiber membrane is thermally imidized to obtain a PI fiber membrane with a pore size of 50 to 200 nanometers.

[0053] The preparation process of the oriented PI fiber membrane with a pore size of 200 to 500 nanometers is as follows: first, 2.5072 g of ODA is dissolved in DMAc under an ice-water bath, and then 2.7393 g of PMDA monomer is gradually added to the above solution, and PAA with a solid content of 10% is prepared by gradual polymerization. The PAA solution obtained by polymerization is transferred to a syringe as a spinning solution, the spinning voltage is set to 20 kV, the distance between the spinning needle and the receiving roller is set to 15 cm, the receiving roller speed is set to 1500 to 2000 rpm, and then the PAA nanofiber membrane is thermally imidized to obtain a PI fiber membrane with a pore size of 200 to 500 nanometers.

[0054] In a feasible implementation, the first outer coating 10 is made of an inorganic material on the upper surface of the composite inner membrane 20 by a scraping process, and the second outer coating 30 is made of an inorganic material on the lower surface of the composite inner membrane 20 by a scraping process.

[0055] Among them, the first outer coating 10 and the second outer coating 30 are both inorganic nano coatings. Exemplarily, the preparation of the inorganic nano coating is as follows: at room temperature, boron nitride inorganic particles with a particle size of 10 to 50 nanometers are placed in a PVDF glue solution with a mass ratio of PVDF to NMP (N-methylpyrrolidone) of 1:20, and the volume content of the boron nitride particles is controlled within the range of 85% to 99%, and then scraped on the upper and lower surfaces of the prepared composite inner membrane 20, thereby obtaining an inorganic nano coating with a pore size of 10 to 50 nanometers.

[0056] Inorganic materials have high hardness and rigidity. Lithium dendrites come into contact with high-rigidity diaphragm materials during their growth. Therefore, high-rigidity inorganic materials can alleviate the growth of lithium dendrites through mechanical hindrance.

[0057] In a feasible implementation, the inorganic material used in the first outer coating layer 10 and the second outer coating layer 30 is boron nitride and / or graphene oxide.

[0058] Among them, the inorganic materials of the first outer coating layer 10 and the second outer coating layer 30 in the present application are preferably boron nitride film and graphene oxide.

[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A composite lithium battery separator, characterized in that: It comprises a first outer coating, a composite inner film and a second outer coating which are stacked in sequence, wherein the first outer coating and the second outer coating are both inorganic nano coatings, and the first outer coating and the second outer coating are coated on the upper and lower surfaces of the composite inner film respectively; The composite inner membrane comprises at least three layers of fiber membranes bonded in sequence, and each layer of the fiber membranes is an oriented nanofiber membrane; Along the center surface of the thickness direction of the composite lithium battery separator and the direction extending to both sides, the pore size of the composite lithium battery separator decreases layer by layer; In the projection of the fiber orientation direction of each layer of the fiber membrane at any point on the central plane, the projections of each orientation direction are evenly distributed in a circle with the arbitrary point as the center.

2. The composite lithium battery separator according to claim 1, characterized in that: The total thickness of the composite lithium battery separator is 25 to 45 microns, and the number of layers of the fiber membrane is 3 to 8.

3. The composite lithium battery separator according to claim 1, characterized in that: The composite inner membrane includes four layers of fiber membranes, and the four layers of fiber membranes are a first fiber membrane, a second fiber membrane, a third fiber membrane and a fourth fiber membrane which are arranged in sequence between the first outer coating layer and the second outer coating layer.

4. The composite lithium battery separator according to claim 3, characterized in that: The pore sizes of the second fiber membrane and the third fiber membrane are 200 to 500 nanometers, the pore sizes of the first fiber membrane and the fourth fiber membrane are 50 to 200 nanometers, and the pore sizes of the first outer coating layer and the second outer coating layer are 10 to 50 nanometers.

5. The composite lithium battery separator according to claim 3, characterized in that: The fiber orientation direction of the first fiber membrane is consistent with the length direction of the composite inner membrane, the fiber orientation direction of the second fiber membrane is at an angle of 45° to the fiber orientation direction of the first fiber membrane, the fiber orientation direction of the third fiber membrane is perpendicular to the fiber orientation direction of the second fiber membrane, and the fiber orientation direction of the fourth fiber membrane is perpendicular to the fiber orientation direction of the first fiber membrane.

6. The composite lithium battery separator according to any one of claims 1 to 5, characterized in that: Each layer of the fiber membrane is made of polyimide material using electrostatic spinning technology.

7. The composite lithium battery separator according to any one of claims 1 to 5, characterized in that: The first outer coating layer is made of an inorganic material on the upper surface of the composite inner film by a scraping process, and the second outer coating layer is made of an inorganic material on the lower surface of the composite inner film by a scraping process.